GELOMBANG BARU MASKULINITAS : PENGARUH BUDAYA K-POP TERHADAP PERSEPSI MASKULINITAS DAN PERILAKU PENGGUNAAN PRODUK KECANTIKAN DI KALANGAN PRIA SURABAYA - Ellyn Dya Lestari; Zumrotul Fitriyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the influence of K-Pop culture on perceived masculinity and beauty product usage behavior among Surabaya men. K-Pop culture, known for its strong visual aesthetics and distinct masculine icons, has become a global phenomenon that influences traditional gender norms. Using a quantitative approach and Partial Least Squares (PLS) method, this study involved 96 male respondents who are exposed to K-Pop culture and use beauty products. The results showed that K-Pop culture has a significant influence on changing perceptions of masculinity, which in turn mediates the use of beauty products. A more inclusive perception of masculinity allows men to embrace self-care without feeling bound by traditional masculinity norms. These findings highlight the importance of popular culture in shaping consumer behavior and offer practical implications for the cosmetics industry to develop more relevant and adaptive marketing strategies. This research also extends the literature on masculinity dynamics and the influence of popular culture in the context of men's consumption behavior in Indonesia.